Data-driven modeling of the flame composition space of an intrinsically unstable lean premixed ammonia/hydrogen/air flame - S. Bottari; F. D’Alessio; C. Matteucci; P.E. Lapenna; F. Creta (Fuel, 2026)

Measurement of the 244Cm neutron capture cross section at the n_TOF facility at CERN - V. Alcayne; A. Kimura; E. Mendoza; D. Cano-Ott; O. Aberle; F. Álvarez-Velarde; S. Amaducci; J. Andrzejewski; L. Audouin; V. Babiano-Suarez; M. Bacak; M. Barbagallo; et al. (Annals of Nuclear Energy, 2026)

Argentina's rejection of 2030 agenda undermines environmental sustainability and human well-being - Javier Nori; Alejandro E.J. Valenzuela; Micaela Camino; Elena Abraham; Gabriela Agostini; Marcelo A. Aizen; Virginia Alonso-Roldán; Julieta R. Arcamone; Yanina Arzamendia; German Baldi; Diego Baldo; Matías C. Baranzelli; et al. (Biological Conservation, 2024)

Impact of precipitation, air temperature and abiotic emissions on gross primary production in Mediterranean ecosystems in Europe - S. Bartsch; A. I. Stegehuis; C. Boissard; J. Lathière; J.-Y. Peterschmitt; I. M. Reiter; T. Gauquelin; V. Baldy; L. Genesio; G. Matteucci; C. Fernandez; B. Guenet (European Journal of Forest Research, 2020)

Tree mineral nutrition is deteriorating in Europe - Mathieu Jonard; Alfred Fürst; Arne Verstraeten; Anne Thimonier; Volkmar Timmermann; Nenad Potočić; Peter Waldner; Sue Benham; Karin Hansen; Päivi Merilä; Quentin Ponette; Ana C de la Cruz; et al. (Global Change Biology, 2015)
The response of forest ecosystems to increased atmospheric CO 2 is constrained by nutrient availability. It is thus crucial to account for nutrient limitation when studying the forest response to climate change. The objectives of this study were to describe the nutritional status of the main European tree species, to identify growth‐limiting nutrients and to assess changes in tree nutrition during the past two decades. We analysed the foliar nutrition data collected during 1992–2009 on the intensive forest monitoring plots of the ICP Forests programme. Of the 22 significant temporal trends that were observed in foliar nutrient concentrations, 20 were decreasing and two were increasing. Some of these trends were alarming, among which the foliar P concentration in F. sylvatica , Q. Petraea and P. sylvestris that significantly deteriorated during 1992–2009. In Q. Petraea and P. sylvestris , the decrease in foliar P concentration was more pronounced on plots with low foliar P status, meaning that trees with latent P deficiency could become deficient in the near future. Increased tree productivity, possibly resulting from high N deposition and from the global increase in atmospheric CO 2 , has led to higher nutrient demand by trees. As the soil nutrient supply was not always sufficient to meet the demands of faster growing trees, this could partly explain the deterioration of tree mineral nutrition. The results suggest that when evaluating forest carbon storage capacity and when planning to reduce CO 2 emissions by increasing use of wood biomass for bioenergy, it is crucial that nutrient limitations for forest growth are considered.

The European carbon balance. Part 3: forests - S. LUYSSAERT; P. CIAIS; S. L. PIAO; E.‐D. SCHULZE; M. JUNG; S. ZAEHLE; M. J. SCHELHAAS; M. REICHSTEIN; G. CHURKINA; D. PAPALE; G. ABRIL; C. BEER; et al. (Global Change Biology, 2010)
We present a new synthesis, based on a suite of complementary approaches, of the primary production and carbon sink in forests of the 25 member states of the European Union (EU‐25) during 1990–2005. Upscaled terrestrial observations and model‐based approaches agree within 25% on the mean net primary production (NPP) of forests, i.e. 520±75 g C m −2 yr −1 over a forest area of 1.32 × 10 6 km 2 to 1.55 × 10 6 km 2 (EU‐25). New estimates of the mean long‐term carbon forest sink (net biome production, NBP) of EU‐25 forests amounts 75±20 g C m −2 yr −1 . The ratio of NBP to NPP is 0.15±0.05. Estimates of the fate of the carbon inputs via NPP in wood harvests, forest fires, losses to lakes and rivers and heterotrophic respiration remain uncertain, which explains the considerable uncertainty of NBP. Inventory‐based assessments and assumptions suggest that 29±15% of the NBP (i.e., 22 g C m −2 yr −1 ) is sequestered in the forest soil, but large uncertainty remains concerning the drivers and future of the soil organic carbon. The remaining 71±15% of the NBP (i.e., 53 g C m −2 yr −1 ) is realized as woody biomass increments. In the EU‐25, the relatively large forest NBP is thought to be the result of a sustained difference between NPP, which increased during the past decades, and carbon losses primarily by harvest and heterotrophic respiration, which increased less over the same period.

Flocculated Amorphous Nanoparticles for Highly Supersaturated Solutions - Michal E. Matteucci; Joseph C. Paguio; Maria A. Miller; Robert O. Williams III; Keith P. Johnston (Pharmaceutical Research, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Curcumin treatment protects rat retinal neurons against excitotoxicity: effect on N-methyl-D-aspartate-induced intracellular Ca2+ increase - A. Matteucci; C. Frank; M. R. Domenici; M. Balduzzi; S. Paradisi; G. Carnovale-Scalzo; G. Scorcia; F. Malchiodi-Albedi (Experimental Brain Research, 2005)

Evaluation of six process‐based forest growth models using eddy‐covariance measurements of CO 2 and H 2 O fluxes at six forest sites in Europe - K. Kramer; I. Leinonen; H. H. Bartelink; P. Berbigier; M. Borghetti; Ch Bernhofer; E. Cienciala; A. J. Dolman; O. Froer; C. A. Gracia; A. Granier; T. Grünwald; et al. (Global Change Biology, 2002)
Reliable models are required to assess the impacts of climate change on forest ecosystems. Precise and independent data are essential to assess this accuracy. The flux measurements collected by the EUROFLUX project over a wide range of forest types and climatic regions in Europe allow a critical testing of the process‐based models which were developed in the LTEEF project. The ECOCRAFT project complements this with a wealth of independent plant physiological measurements. Thus, it was aimed in this study to test six process‐based forest growth models against the flux measurements of six European forest types, taking advantage of a large database with plant physiological parameters. The reliability of both the flux data and parameter values itself was not under discussion in this study. The data provided by the researchers of the EUROFLUX sites, possibly with local corrections, were used with a minor gap‐filling procedure to avoid the loss of many days with observations. The model performance is discussed based on their accuracy, generality and realism. Accuracy was evaluated based on the goodness‐of‐fit with observed values of daily net ecosystem exchange, gross primary production and ecosystem respiration (gC m −2 d −1 ), and transpiration (kg H 2 O m −2 d −1 ). Moreover, accuracy was also evaluated based on systematic and unsystematic errors. Generality was characterized by the applicability of the models to different European forest ecosystems. Reality was evaluated by comparing the modelled and observed responses of gross primary production, ecosystem respiration to radiation and temperature. The results indicated that: Accuracy . All models showed similar high correlation with the measured carbon flux data, and also low systematic and unsystematic prediction errors at one or more sites of flux measurements. The results were similar in the case of several models when the water fluxes were considered. Most models fulfilled the criteria of sufficient accuracy for the ability to predict the carbon and water exchange between forests and the atmosphere. Generality. Three models of six could be applied for both deciduous and coniferous forests. Furthermore, four models were applied both for boreal and temperate conditions. However, no severe water‐limited conditions were encountered, and no year‐to‐year variability could be tested. Realism. Most models fulfil the criterion of realism that the relationships between the modelled phenomena (carbon and water exchange) and environment are described causally. Again several of the models were able to reproduce the responses of measurable variables such as gross primary production (GPP), ecosystem respiration and transpiration to environmental driving factors such as radiation and temperature. Stomatal conductance appears to be the most critical process causing differences in predicted fluxes of carbon and water between those models that accurately describe the annual totals of GPP, ecosystem respiration and transpiration. As a conclusion, several process‐based models are available that produce accurate estimates of carbon and water fluxes at several forest sites of Europe. This considerable accuracy fulfils one requirement of models to be able to predict the impacts of climate change on the carbon balance of European forests. However, the generality of the models should be further evaluated by expanding the range of testing over both time and space. In addition, differences in behaviour between models at the process level indicate requirement of further model testing, with special emphasis on modelling stomatal conductance realistically.

Productivity overshadows temperature in determining soil and ecosystem respiration across European forests - I. A. Janssens; H. Lankreijer; G. Matteucci; A. S. Kowalski; N. Buchmann; D. Epron; K. Pilegaard; W. Kutsch; B. Longdoz; T. Grünwald; L. Montagnani; S. Dore; et al. (Global Change Biology, 2001)
Summary This paper presents CO 2 flux data from 18 forest ecosystems, studied in the European Union funded EUROFLUX project. Overall, mean annual gross primary productivity (GPP, the total amount of carbon (C) fixed during photosynthesis) of these forests was 1380 ± 330 gC m −2 y −1 (mean ±SD). On average, 80% of GPP was respired by autotrophs and heterotrophs and released back into the atmosphere (total ecosystem respiration, TER = 1100 ± 260 gC m −2 y −1 ). Mean annual soil respiration (SR) was 760 ± 340 gC m −2 y −1 (55% of GPP and 69% of TER). Among the investigated forests, large differences were observed in annual SR and TER that were not correlated with mean annual temperature. However, a significant correlation was observed between annual SR and TER and GPP among the relatively undisturbed forests. On the assumption that (i) root respiration is constrained by the allocation of photosynthates to the roots, which is coupled to productivity, and that (ii) the largest fraction of heterotrophic soil respiration originates from decomposition of young organic matter (leaves, fine roots), whose availability also depends on primary productivity, it is hypothesized that differences in SR among forests are likely to depend more on productivity than on temperature. At sites where soil disturbance has occurred (e.g. ploughing, drainage), soil espiration was a larger component of the ecosystem C budget and deviated from the relationship between annual SR (and TER) and GPP observed among the less‐disturbed forests. At one particular forest, carbon losses from the soil were so large, that in some years the site became a net source of carbon to the atmosphere. Excluding the disturbed sites from the present analysis reduced mean SR to 660 ± 290 gC m −2 y −1 , representing 49% of GPP and 63% of TER in the relatively undisturbed forest ecosystems.